2012
DOI: 10.1155/2012/343742
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole-Vincristine Coadministration Triggers Seizure in a Young Female Adult: A Case Report

Abstract: Coadministration of azoles and vincristine has been shown to increase vincristine neurotoxic effects due to the inhibition of cytochrome P450 (CYP) isoform 3A4, for which vincristine is a substrate. Despite the absence of any casual relationship between seizure and coadministration of azoles, few case reports of vincristine-induced seizure have been documented after coadministration of fluconazole or posaconazole in children. In this paper we are reporting the first young female adult who experienced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The doses were administered by the nurses and 18 patients were found compliant to the therapy. In 18 cases PSZ treatment was not interrupted due to adverse effects; one out of five patients who received vincristine based chemotherapy developed seizures and PSZ treatment was stopped 4. Two patients developed mild breakthrough oral thrush while on PSZ prophylactically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doses were administered by the nurses and 18 patients were found compliant to the therapy. In 18 cases PSZ treatment was not interrupted due to adverse effects; one out of five patients who received vincristine based chemotherapy developed seizures and PSZ treatment was stopped 4. Two patients developed mild breakthrough oral thrush while on PSZ prophylactically.…”
Section: Resultsmentioning
confidence: 99%
“…PSZ possesses CYP3A4 inhibition capacity in gut and liver which increases its potential for drug–drug interactions 7 9. Recently, few case studies have reported that co-administration of PSZ and vincristine increased the latter's serious neurotoxic side effects 4 10 11. PSZ is well tolerated in renal and hepatic impaired patients with no recommended dosage adjustments 7 12 13.…”
Section: Introductionmentioning
confidence: 99%
“…ALL treatment show higher cure rates in children than adults and involves a complex and intensive therapy program. Said R et al [ 1 ] vincristine (VCR) is an antineoplastic agent that acts by inhibiting microtubule formation in the miotic spindle causing cell death that may be accompanied by neurological side effect [ 2 , 3 ]. It represents a key component in the ALL in children and adults and is currently the backbone of the induction, intensification, and consolidation phases in the treatment of this disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…VCR clinical efficacy is significantly dependent on its concentration and duration of exposure [ 1 ]. Unfortunately, it carries the potential for neurological toxicity that is both dose and duration dependent and is characterized by neuropathy, paresthesia, sensory deficits, muscle weakness, and rarely seizures [ 3 , 6 ]. Hence, minimal alterations in VCR plasma concentrations might have serious consequences on its efficacy as well as its neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Those neurotoxic symptoms usually appear as constipation and peripheral neurotoxicity [ 3 ]. In addition, few case reports have illustrated the possible exacerbation of VCR toxicity by coadministration of PSZ in children and young adults where fluctuations in level of consciousness and seizures have been observed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%